2016
DOI: 10.1002/phar.1831
|View full text |Cite
|
Sign up to set email alerts
|

Community Pharmacists Assisting in Total Cardiovascular Health (CPATCH): A Cluster‐Randomized, Controlled Trial Testing a Focused Adherence Strategy Involving Community Pharmacies

Abstract: The CPATCH intervention was ineffective for improving patient adherence to statin therapy in community pharmacies. However, poor effectiveness may have resulted from a failure to deliver the protocol consistently in several intervention pharmacies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 23 publications
(30 reference statements)
0
12
0
Order By: Relevance
“… 25 – 32 Three studies found no overall effect on adherence. 33 35 Two studies found a significant gender-specific intervention effect, 31 , 34 whilst the other nine studies found no gender-specific effects, ie, the intervention was equally effective (or ineffective) for men and women. Four studies were multicomponent studies versus eleven single component studies (see Table 1 ).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“… 25 – 32 Three studies found no overall effect on adherence. 33 35 Two studies found a significant gender-specific intervention effect, 31 , 34 whilst the other nine studies found no gender-specific effects, ie, the intervention was equally effective (or ineffective) for men and women. Four studies were multicomponent studies versus eleven single component studies (see Table 1 ).…”
Section: Resultsmentioning
confidence: 98%
“…Patients were asked to respond whether they had taken their medication, whether the text reminded them, and the reason if they had not taken their medication. Ineffective Interventions (neither a gender-neutral nor a gender-specific intervention effect) Blackburn, 2016 Canada 35 Cluster RCT 1,906 new statins users. Intervention group: n=907 (♀ n=447) Control group: n=999 (♀ n=431) Type: single component; counseling Setting: community pharmacy Aim: prevent nonadherence during the first year of statin use Two brief screening questions: 1) “How long have you been taking this medication?” 2) (example) “Are you having any difficulties or concerns with this new medication?” Pharmacists were challenged to personalize the second screening question.…”
Section: Resultsmentioning
confidence: 99%
“…The median Cochrane risk of bias score by individual paper was 50.0% (IQR 33.3–66.7). Only one paper met all criteria of the Cochrane tool and two papers did not meet any. The median CONSORT score was 59.5% (IQR 52.0–70.3%) with three papers meeting 83.8% of the criteria and one meeting only 29.7% .…”
Section: Resultsmentioning
confidence: 99%
“…Collaborating with all relevant stakeholders in services research and development, with the patients’ best interest as the main priority, will require a change of mindset on both individual and organizational level. Allowing community pharmacists to fully engage in services provision and research, and providing them with enough information and support to do so can ultimately make the significant difference regarding patient outcome …”
Section: Discussionmentioning
confidence: 99%
“…Allowing community pharmacists to fully engage in services provision and research, and providing them with enough information and support to do so can ultimately make the significant difference regarding patient outcome. [35] From a professional perspective, the pharmacists regard themselves as lacking the competence required for CPS provision and research, but also as overqualified for their regular day-to-day activities. They appear to need CPSs and CPS research to allow them to use their skills, properly counsel patients and develop professionally.…”
Section: Discussionmentioning
confidence: 99%